Fostering Religious Character Through Malam Bina Iman dan Taqwa (MABIT) Program at SMP IT Al-Ghazali Jember - ida, nur_dzaedzatul_hikmah; Saiful Amien; Moh. Nurhakim (IKIP PGRI Bojonegoro, 2025)
The development of students' religious character is an essential aspect in Islamic education, especially in facing the challenges of modernization and globalization that impact the moral behaviour of the younger generation. This study aims to analyze the implementation and effectiveness of the Malam Bina Iman dan Taqwa (MABIT) program at SMP IT Al-Ghazali Jember as a strategy for fostering students' religious character. This research uses a qualitative approach with a case study design, where data is obtained through in-depth interviews, participatory observation, and documentation. The primary informants included the principal, accompanying teachers, and students from various grade levels. The triangulation technique was applied to ensure data credibility. The results showed that the MABIT program significantly improved students' daily worship discipline, independence, and responsibility. The activities in this program - including congregational worship, religious studies, group discussions, and self-muhasabah - contribute to forming stronger religious characters. The evaluation of the program shows that its effectiveness is influenced by the active involvement of teachers and parents, as well as the continuity of the activities carried out. The implications of this study indicate that character education based on direct experience is more effective than theoretical approaches, and coaching models such as MABIT need to be developed further. Recommendations include periodic evaluation of learning methods, student participation optimization, and technology integration to support program sustainability.